Strengthening The Functions of Savings Guarantee Institutions for Increased Protection of Customers and Insurance Policy Holder - Jonker Sihombing (Faculty of Law, Universitas Pekalongan, 2023)
Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector amended the provisions relating to the Deposit Insurance Corporation revised clauses related to the Deposit Insurance Corporation. Earlier clauses covered bank customer deposits, it broadened to encompass insurance policies. This research delves into understanding how roles, responsibilities, powers of the Deposit Insurance Corporation bolstered with the introduction of this Law, aiming to better safeguard depositors and insurance policyholders. Normative juridical approach forms the backbone of this research. Secondary data is the primary source of information, with primary legal documents like laws, regulations supplemented by secondary legal resources such as books, literature, academic journals. Findings indicate this Law provides depositors with assurance regarding security of their deposits in the event a bank is deemed to be resolute, deposit repayments process are more transparent. Insurance policyholders benefit as the law now clearly outlines the claim repayment.